Kualitas Jaringan Internet Pada Bank Tabungan Negara (BTN) (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
With the development of technology, the speed of access to information is increasingly needed. The network is not only connected but also must be stable, fast, and smooth. Therefore, it is necessary to build a system that divides the bandwidth for each employee of an organization/office using a router. In this study, a bandwidth management system will be created that divides the bandwidth of 30 Mbps for employees at Bank BTN. This can be done by ensuring that every user who accesses the internet will get the same bandwidth allocation on the network. The system's design aims to make downstream speeds by limiting the internet access used at the BTN bank office for each employee. Based on the research that has been done, the best throughput results for employees in the morning on the third day are 91% with an index of 4 and a very good category. While the worst throughput results for employees in the morning on the first day were 81%, with an index of 4 and a very good category. Moreover, the overall throughput results obtained an average of 84% with an index of 4 and a very good category.Keyword: Bandwidth, Quality of service, Througput.